Bandgap Engineering of TiO2 for Enhanced Selectivity in Photoelectrochemical Glycerol Oxidation - Claudio M. Pecoraro; Siming Wu; Monica Santamaria; Patrik Schmuki (Advanced Materials Interfaces)
Abstract The application of photoelectrochemical cells to the partial oxidation of biomass represents a promising avenue as a sustainable process for obtaining valuable products. However, achieving both efficient conversion rates and high selectivity of desired products remains a great challenge. In this study, the photoelectrochemical oxidation of glycerol is investigated to produce dihydroxyacetone (DHA) as the primary target using TiO2 nanotubes (NTs) as the photoanode. Nitrogen doping is used to modify the TiO2 NTs, resulting in enhanced visible light photoactivity in N‐doped NTs. These N‐doped NTs exhibit a high selectivity toward DHA and show a remarkable faradaic efficiency when irradiated with light at a wavelength of 450 nm, i.e., light that excites N‐related states in the band gap of TiO2. The N‐doped material also exhibits remarkable stability over prolonged reaction periods. The superior performance of N‐doped NTs can be attributed to the band‐engineering effects induced by nitrogen doping. Specifically, N‐doping leads to an upward shift of the valence band, thereby adjusting the exit energy levels of photogenerated holes that result in a high selectivity toward glycerol conversion to DHA.